Pedometer determined physical activity level and its associated factors among type 2 diabetes mellitus patients attending a university primary care clinic / Khairatul Nainey Kamaruddin - Kamaruddin, Khairatul Nainey (2018)
Physical activity exerts many positive health benefits for patients with type 2 diabetes mellitus (T2DM). Exercise exerts an immediate effect of increasing insulin sensitisation while regular exercises reduce symptoms of depression and improved health-related quality of life, a common problem in those with T2DM. While there is extensive evidence on physical activity assessment among T2DM patients worldwide, however locally, there is a lack of objective physical activity measurement among Malaysian T2DM population. This study aims to assess the physical activity level based on average steps/day and its associated factors among T2DM patients attending a university primary care clinic. A cross-sectional study was conducted between January 2017 and August 2017 in Primary Care Medicine Clinic, UiTM Selayang Campus. Using convenient sampling, patients who were more than 18 years old and was diagnosed with T2DM for least for six months were recruited, Information on sociodemographic characteristics, anthropometry measurements and related clinical data were recorded in a proforma. Patients were monitored of their regular daily physical activity using a pedometer, a wearable steps tracker for the whole day, starting from early morning get up until bedtime at night for seven consecutive days, Every patient was given detailed instruction on the handling of the pedometer and three reminders in the form of text messages or phone calls to remind them to wear the pedometer. A text message was given on day seven to remind them to return the pedometer on the day eight. Upon receiving the pedometer, the researcher read and record the number of steps taken for each day.